Early experience with ultrasound guided pneumatic reduction of intussusception using locally assembled equipment in Nepal - Adhikari, Suman Bikram (Journal of Society of Surgeons of Nepal, 2019)
Introduction: Intussusception is one of the commonest emergency conditions in children. Pneumatic reduction of intussusception, a minimally invasive technique, has a higher success rate and lower incidence of complications as compared to barium enema & hydrostatic reduction and also omits the need for unnecessary laparotomy. The aim of this study was to evaluate the results of the pneumatic reduction in our hospital as a treatment of idiopathic pediatric ileocolic intussusception and to identify the pretreatment factors associated with pneumatic reduction failure. Methods: This was a prospective analytical study. A total of 12 children were enrolled in the study between January to November 2018 at Nepal National Hospital, Kathmandu. Patients were given air enema under Ultrasound-guidance, using locally assembled equipment. All procedures were performed under intravenous anesthesia. The intraluminal pressure was monitored with a pressure gauge and was not permitted to go above 100 mmHg. A total of three attempts of 3 minutes each were allowed. Results: Average age of the patients was 2.7 years, with a male-female ratio of 3:1. Eleven (92%) of the cases were successfully reduced while 1 (8%) case failed to reduce. No bowel perforation occurred in this study. The mean duration of symptoms before presentation was 42 hours. The mean length of intussusceptum was 3.058 cm. the mean duration of pneumatic reduction was 1.97 minutes and total intervention time i.e. from induction of anesthesia to reversal from anesthesia was 18.55 minutes. Conclusion: The technique described is easy to assemble, safe and effective. I recommend it for regular use in pneumatic reduction of intussusception, especially in centers with limited resources.